Aldehyde Dehydrogenase-1A1 (ALDH1A1): The Novel Regulator of Chemoresistance in Pancreatic Cancer Cells - Hong-Quan Duong PhD; Minh-Cong Hoang MSc; Thi-Hue Nguyen MSc; Phuong-Thoa Nguyen MSc; Van-Thu Le MSc; Thi-Nguyet Dao MSc; Van-Lang Ngo MSc; The-Hung Dang PhD (Cancer Control)
Aldehyde dehydrogenase-1A1 (ALDH1A1), a member of a superfamily of 19 isozymes, exhibits various biological functions and is involved in several important physiological and pathological processes, including those associated with various diseases including cancers such as pancreatic cancer. Chemotherapy is one of the most important strategies for the treatment of pancreatic cancer; however, the chemoresistance exhibited by pancreatic cancer cells is a leading cause of chemotherapy failure. It has been reported that overexpression of ALDH1A1 significantly correlates with poor prognosis and tumor aggressiveness, and is clinically associated with chemoresistance. Additionally, ALDH1A1 may serve as a novel regulator for the diagnosis and prognosis of cancer resistance. In particular, ALDH1A1 can promote cancer progression by facilitating the manifestation of cancer stem cell properties. However, the molecular mechanism by which ALDH1A1 clinically regulates the development of chemoresistance, and its role in prognosis and cancer stem cells, including pancreatic cancer stem cells, remain unclear. Therefore, the current review aims to summarize the clinical functions of ALDH1A1 as a novel regulator of chemoresistance, prognosis, and cancer stem cell development in pancreatic cancer.